The impact of medical staff’s character strengths on job performance in Hangzhou hospitals - Zhou, Xin; Zhang, Yinrui; Wang, Yuhang; Wang, Haixia; Sun, Shuaijun; Huang, Xianhong (Frontiers in Psychology, 2023)
Background Improving job performance has a significant effect on the quality of medical services and ensuring people’s health. Purpose This study explores the influence and mechanism of the character strengths and career callings of medical staff as well as the intermediary role of such career calling. Methodology A cross-sectional survey was conducted of 414 healthcare staff members in public hospitals in Hangzhou. Descriptive statistics and hierarchical linear regressions were used to analyze the medical staff’s job performance and related factors, and structural equation modeling path analysis was used to explore and validate the influence and mechanism of character advantage and career calling on job performance. Results The results show that medical staff character strengths have a positive impact on job performance. Path analysis shows that character strengths indirectly affect job performance, and career calling plays a partial mediating role in character strengths and job performance. Conclusion The results show that good personalities promote job performance, and the association is more significant under a high sense of career calling.